Pengaruh Dimensi Kualitas Pelayanan terhadap Kepuasan Siswa di MTS Mathla’ul Anwar Seribu Pesawaran - Dewanti Nurul Azizah; Nurdin Nurdin; Albet Maydiantoro (FKIP Universitas Lampung, 2020)
The Effect of Service Dimensions on Student Satisfaction at MTs Mathla'ul Anwar Seribu Pesawaran. This study aims to see the effect of service dimensions (tangibility, reliability, responsiveness, assurance, and empathy) on student satisfaction. This study population were students of class VII-IX MT Mathath'ul Anwar Pesawaran 2019-2020. In this study, 90 people were used. Sampling is determined by probability sampling using the simple random sampling method. So that the number of samples obtained in this study were 73 people. The analysis technique used is the hypothesis test t-test and F test. This research uses descriptive methods of verification and input. This study indicates that the quality of service at MTs Mathla'ul Anwar Pesawaran, reliability, responsiveness, assurance, and empathy have a significant effect on student satisfaction.Kata Kunci: Dimensi Kualitas Pelayanan, Kepuasan Siswa, MTs Mathla’ul Anwar.http://dx.doi.org/10.23960/E3J/v3i2.pp81-88